Management Whitepaper: Examining the Development of a Social Media Strategy for a National Sport Organisation: A Case Study of Tennis New Zealand - Ashleigh-Jane Thompson; Andrew J. Martin; Sarah Gee; Andrea N. Eagleman (Journal of Applied Sports Management, 2014)
Research Problem The purpose of this paper was to examine the development and maintenance of a social media strategy for a National Sport Organisation (NSO) in New Zealand. This research contains information that highlights a number of issues surrounding the development and effective utilisation of social media for an NSO, in particular applying a “one-size-fits-all” approach to its management. Other issues included constant Facebook-induced changes, lack of current social media knowledge and understanding at an organisational and sector level, and the ability to sustain an online presence. This article would likely be useful to NSOs and other stakeholders of sport organisations, particularly those involved with or considering developing a social media strategy.